1999
DOI: 10.1038/23236
|View full text |Cite
|
Sign up to set email alerts
|

The origin of snake feeding

Abstract: whereas there is clearly not enough time for a 40-kyr obliquity control, thus excluding glacio-eustasy. Evaporite deposition occurred during precession maxima (insolation minima), during relatively dry periods when evaporation exceeded precipitation. This allowed the Mediterranean to form a giant brine, when out¯ow of dense Mediterranean waters into the Atlantic was restricted or obstructed by shallow sills in the western Mediterranean gateways. During precession minima (insolation maxima) and relatively wet p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 16 publications
1
50
0
Order By: Relevance
“…Similarly, a majority of recent analyses have placed snakes within Anguimorpha, although their precise relationships continue to be fiercely debated (e.g. Rieppel, 1988a,b;Caldwell & Lee 1997;Lee, 1997Lee, , 1998Lee & Caldwell, 1998Caldwell, 1999;Lee, Bell & Caldwell, 1999;Zaher & Rieppel, 1999;Cundall & Greene, 2000;Rage & Escuillié, 2000;Rieppel & Zaher, 2000 a, b;Tchernov et al, 2000;Rieppel & Kearney, 2001; see Coates & Ruta, 2000 for a comprehensive and impartial review).…”
Section: (C) Iguaniamentioning
confidence: 96%
“…Similarly, a majority of recent analyses have placed snakes within Anguimorpha, although their precise relationships continue to be fiercely debated (e.g. Rieppel, 1988a,b;Caldwell & Lee 1997;Lee, 1997Lee, , 1998Lee & Caldwell, 1998Caldwell, 1999;Lee, Bell & Caldwell, 1999;Zaher & Rieppel, 1999;Cundall & Greene, 2000;Rage & Escuillié, 2000;Rieppel & Zaher, 2000 a, b;Tchernov et al, 2000;Rieppel & Kearney, 2001; see Coates & Ruta, 2000 for a comprehensive and impartial review).…”
Section: (C) Iguaniamentioning
confidence: 96%
“…mosasaurs, Tethysaurus Bardet et al, 2003 and aigialosaurs) and other reptiles remain controversial. Many workers (e.g., deBraga & Carroll, 1993) favour the idea that the mosasauroids are derived varanoid lizards (i.e., within the order Sauria), although recent studies (e.g., Lee et al, 1999) have revived an old theory (e.g., Cope, 1869) that the mosasauroids form a sister group to modern snakes (order Ophidia). Russell (1967) suggested that two ancestral lineages of the Mosasauridae; one Clidastes-like and one Platecarpus-like, gave rise to all subsequent mosasaur taxa.…”
Section: Discussionmentioning
confidence: 99%
“…The 'smoking gun' that clinched this explanation (Cleland 2002) was the discovery of corresponding home site marks on the inside of the body chamber of a Cretaceous ammonite, associated with radula scrape marks and with a limpet shell (Seilacher 1998). Under pressure from the theoretical preconception that snakes are descended from mosasauroids, however, Lee et al (1999) used the putative mosasaur bite marks on the ammonite first described by Kauffman and Kesling (1960) to reconstruct jaw movements in mosasaurs. Their conclusion was that the jaw movements of mosasaurs corresponded to a pattern that is intermediate between that of terrestrial lizards and snakes such as pythons.…”
Section: Trees Versus Charactersmentioning
confidence: 97%